Islamic ethical paradigm on poor compliance in the management of bronchial asthma - Mahamad Fuad, Syafiqah Izzati; Taib, Fahisham; Hasan, Taufiq Hidayat (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Childhood asthma is known to cause heavy economic burden due to increased hospital visits and prolonged hospital care due to its exacerbations. Despite the advancement of in-hospital management to control asthma, poor compliance has been an astounding problem in the management of the acute asthma attack. An 8-year-old boy, who was known as persistent bronchial asthma since 5 year of age, have had frequent visits to the clinics and hospital due to poorly controlled asthma symptoms. During this episode, he presented with worsening shortness of breath. He often misses his daily medication due to parental assumption that the patient is able to manage asthma by himself. His non-compliance towards medications has led to patient’s absenteeism from school and deterioration in his academic performance. Islam is a religion that emphasizes on provision of individual’s and community’s health. This is achieved through taking an optimal care of one’s health and aimed at maintaining disease control state. Parents have the duty to provide their children with good and healthy living throughout the childhood period, and not to neglect them in any way. Islam stresses the importance not only self-care in the society but also preservation of others’ health especially by the Muslim doctors. Conservation and protection of individual’s right to health especially children require group effort of both parents and medical personnel.